The Laboratory Diagnosis of Autoimmune Encephalitis - Lee, Sang Kun (J Epilepsy Res, 2016)
Autoimmune encephalitis is a group of encephalitis syndromes that cause altered mentality, memory decline, or seizures in association with the presence of serum and cerebrospinal fluid (CSF) autoantibodies (auto-Abs). An early diagnosis enables early treatments. The detection of auto-Abs is a confirmatory diagnosis. Tissue-based assay, cell-based immunoassay, and immunoblotting are used to detect various autoantibodies. The CSF test for the presence of antibodies is important because it is more sensitive and reflects disease activity in many autoimmune encephalitis, although antibody tests can be negative even in the presence of autoimmune encephalitis. EEG is often abnormal, but nonspecific. A unilateral or bilateral medial temporal T2 high signal is a common finding in MRI. Fludeoxyglucose-positron emission tomography is sometimes useful for diagnosis in patients with normal MRI.